2013
DOI: 10.1016/j.curtheres.2012.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Kidney Biopsy Data From a Single Center in the Midland Rural Area of China, 1996–2010

Abstract: ObjectiveTo survey the clinical epidemiology and correlations between pathology and clinical features of major groups of kidney diseases in a rural area of China.MethodsFrom January 1996 to December 2010, histologic diagnosis of renal disease was made on samples collected from 919 patients from a single center in the midland rural area of China. Demographic data were obtained from all patients, and clinical profiles were analyzed in 917 patients.ResultsThe mean age of the whole group was 33.13 (14.13) years (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…In the present study, the male to female ratio was 1.7:1 which is similar to various Indian and international studies [7][8][9][10]. Although there was an overall male preponderance, both in the groups under 40 years of age, females were more in number than males.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the male to female ratio was 1.7:1 which is similar to various Indian and international studies [7][8][9][10]. Although there was an overall male preponderance, both in the groups under 40 years of age, females were more in number than males.…”
Section: Discussionsupporting
confidence: 90%
“…There was no doubt that primary GD was the most common renal diseases, accounting for 81.55% in our study, and it was within the range of 61.7-82.7% reported from other centers in China. 4,5,8,25,26 No significant change in the prevalence of primary GD was found in our study, while the prevalence of secondary GD increased (9.13% in period 1 versus 14.15% in period 4) (p < 0.05), probably because of the improvement in the recognition of these diseases and diagnostic technology, and its substantial change as well. The frequency of IgAN was markedly different because of regional differences, with the highest in Asian countries (36.7-54.3%), [4][5][6][7][8] Nevertheless, we found that there was a gradual increase in MCD, from 0.34% in period 2 to 2.68% in period 4 (p < 0.001), and this phenomenon could be observed in other study of China.…”
Section: Discussionmentioning
confidence: 42%
“…It has been reported that NS was the main indication for renal biopsy in other countries 10,12,14,22 and northern China. 4,24,26 However, in our study, we found that proteinuria and hematuria rather than NS was the most frequent cause for renal biopsy, making up almost half of the patients (49.03%), and NS ranked the second (20.36%). There was no doubt that primary GD was the most common renal diseases, accounting for 81.55% in our study, and it was within the range of 61.7-82.7% reported from other centers in China.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations